Implementasi Prinsip Syariah dalam Akad Asuransi Syariah - Hafsah, Sariyah; Kurniawati, Fitri (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2025)
Sharia insurance is an insurance system that adheres to Islamic law in the process of its application and operation. Sharia insurance is a type of insurance that minimizes risk and reduces uncertainty. In every operation, including in the implementation of its contract, sharia insurance must adhere to sharia principles as contained in the Qur'an, hadith, and fatwa. To find out what principles need to be implemented in sharia insurance, this study was conducted with the aim of describing sharia principles in sharia insurance contracts. This research is a type of descriptive qualitative research. The results of this study show that this insurance has principles that must be held in its contract operations, namely unity, justice, ta'awun, cooperation, prohibition of usury, gharah, maisir.